2014
DOI: 10.1111/add.12682
|View full text |Cite
|
Sign up to set email alerts
|

The impact of methadone maintenance therapy on hepatitis C incidence among illicit drug users

Abstract: Aims To determine the relationship between methadone maintenance therapy (MMT) and hepatitis C (HCV) seroconversion among illicit drug users. Design Generalized Estimating Equation model assuming a binomial distribution and a logit link function was used to examine for a possible protective effect of MMT use on HCV incidence. Setting Data from three prospective cohort studies of illicit drug users in Vancouver, Canada between 1996 and 2012. Participants 1004 HCV antibody negative illicit drug users strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(104 citation statements)
references
References 49 publications
5
97
1
1
Order By: Relevance
“…In total, we included 21 published studies 14,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] and seven unpublished studies [33][34][35][36][37]59,60 comprising 1827 HCV incident infections and 8789.7 person-years of follow-up. Overall HCV infection incidence ranged between 0.09 and 42 cases per 100 person-years across the studies.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, we included 21 published studies 14,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] and seven unpublished studies [33][34][35][36][37]59,60 comprising 1827 HCV incident infections and 8789.7 person-years of follow-up. Overall HCV infection incidence ranged between 0.09 and 42 cases per 100 person-years across the studies.…”
Section: Study Selectionmentioning
confidence: 99%
“…Twenty-one of the included studies reported the impact of OST, 14,20,39,40,[45][46][47]49,[51][52][53]55,57,58 including seven unpublished estimates. [33][34][35][36][37]59,60 Seventeen studies reported the impact of NSPs, 14,20,[41][42][43][44]47,48,50,54,56,58 including five unpublished sources, [33][34][35]59,60 and four reported combined measures of NSPs with OST, 14,33,44,47 including one unpublished data source.…”
Section: Type Of Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Access to substance use treatment is also considered key in harm reduction. For opiate users, receipt of opiate substitution treatment (OST) has been demonstrated to have positive impacts on risky injection behaviours (MacArthur, et al, 2014) and more recently, on HCV seroconversion (Nolan, et al, 2014;Tsui, Evans, Lum, Hahn, & Page, 2014), though limited evidence exists in support of other addiction treatment interventions (e.g., outpatient drug-free programs) (Hagan, Pouget, & Des Jarlais, 2011). In parallel, timely HCV screening, counseling and testing constitute essential actions for prevention (Centers for Disease Control and Prevention, 2012), as they have the potential to impact HCV acquisition and transmission rates by reducing high-risk drug use practices Bruneau, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%